2013
DOI: 10.1111/chd.12098
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Venous Hemostasis in Children Using the Technique of “Figure-of-Eight” Sutures

Abstract: The "figure-of-eight" suture technique is effective and safe, achieving immediate hemostasis after the use of large femoral vein sheaths in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The beauty of the F08 technique is that it simple and easy to learn and the results of the study by Lakshmanadoss et al. clearly support the safety and utility of the F08 technique and corroborates those of previous investigators [11] , [15] , [16] , [17] . The shorter time on bed rest has definite clinical implications in terms of patient comfort, hospital stay and implied healthcare cost.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The beauty of the F08 technique is that it simple and easy to learn and the results of the study by Lakshmanadoss et al. clearly support the safety and utility of the F08 technique and corroborates those of previous investigators [11] , [15] , [16] , [17] . The shorter time on bed rest has definite clinical implications in terms of patient comfort, hospital stay and implied healthcare cost.…”
supporting
confidence: 77%
“…The figure of eight (FO8) suture was first described with structural heart disease interventions in children but more recent reports point to this technique being a cost-effective hemostatic method after catheter ablation of AF [14] , [15] , [16] . The technique involves caudal (deep) to cranial (superficial) suture around the sheath(s) insertion site(s) including the subcutaneous tissue but avoiding the femoral vessels to plug the venotomy [14] .…”
mentioning
confidence: 99%
“…Morgan et al and Zhou et al published a case series demonstrating feasibility and safety of the “Z”‐stitch in children after structural interventions using 6–22 F sheath . More recently, three other nonrandomized studies confirmed safety and efficacy of the method in patients undergoing catheter ablation of atrial fibrillation with the use of 15 F sheaths .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using venography and vascular ultrasound imaging modalities had demonstrated the safety and efficacy of the F-8 suture technique for femoral venous hemostasis [10][11][12][13][14][15]. This technique produces compression the femoral vein at the sheath entry point by the external soft tissue to achieve hemostasis, without causing thrombus, embolism, or venous stenosis.…”
Section: Prior Studies Of the F-8 Suture Techniquementioning
confidence: 99%